2022
DOI: 10.1136/jech-2022-219200
|View full text |Cite
|
Sign up to set email alerts
|

Completeness and representativeness of small area socioeconomic data linked with the UK Clinical Practice Research Datalink (CPRD)

Abstract: BackgroundThe Clinical Practice Research Datalink (CPRD) holds primary care electronic healthcare records for 25% of the UK population. CPRD data can be linked via practice postcode in the UK, and additionally via patient postcode in England, to area-level socioeconomic status (SES) data including the Index of Multiple Deprivation (IMD), the Carstairs Index and the Townsend Deprivation Index; as well as rural–urban classification (RUC). This study aims to describe the completeness and representativeness of CPR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…We considered the number of hospitalizations in the year before cohort entry as a surrogate marker for overall health. Finally, we adjusted for socioeconomic status using the Index of Multiple Deprivation, categorized in deciles …”
Section: Methodsmentioning
confidence: 99%
“…We considered the number of hospitalizations in the year before cohort entry as a surrogate marker for overall health. Finally, we adjusted for socioeconomic status using the Index of Multiple Deprivation, categorized in deciles …”
Section: Methodsmentioning
confidence: 99%
“…This retrospective cohort study (GSK ID: 213951) used de‐identified, coded medical and prescription records from the Clinical Practice Research Datalink (CPRD) Aurum database with Hospital Episodes Statistics (HES) linkage in the UK (between 1 January 2007 and 30 June 2019). CPRD database populations including CPRD Aurum are considered highly complete and broadly representative of the broader English population, in terms of factors such as geographical spread, age, gender, socioeconomic status and rural–urban classification 21,22 . Linked HES data comprised of medical records on hospital admissions and outpatient visits from the Admitted Patient Care (APC) and Outpatient (OP) HES databases, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The analyses were adjusted for potential covariates at the individual level including the Cambridge Multimorbidity Score (general outcome based on 37 long-term conditions),28 the number of GP consultations in the last 2 years, neighbourhood socioeconomic deprivation level divided into deciles (based on the national Index of Multiple Deprivation,29 30 whether the patient had or had not received a medication review within the last year prior the index date, gender and age (categorised between 30 and 49, between 50 and 64, between 65 and 84, and those 85 or older). The analyses on medication adherence were also adjusted for the number of medicines a patient was prescribed.…”
Section: Methodsmentioning
confidence: 99%